# What is Hess's law of heat summation?

##### 1 Answer

Hess's law of heat summation states that the total enthalpy change during a reaction is the same whether the reaction takes place in one step or in several steps.

For example, in the above diagram,

In Hess's Law calculations, you write equations to make unwanted substances cancel out.

Sometimes you have to reverse an equation to do this, and you reverse the sign of

Sometimes you have to multiply or divide a given equation, and you do the same thing to the

**EXAMPLE**

Determine the heat of combustion,

- C(s) + O₂(g) → CO₂(g);
#ΔH_"c"# = -393.5 kJ - S(s) + O₂(g) → SO₂(g);
#ΔH_"c"# = -296.8 kJ - C(s) + 2S(s) → CS₂(l);
#ΔH_"f"# = 87.9 kJ

**Solution**

Write down the target equation, the one you are trying to get.

CS₂(l) + 2O₂(g) → CO₂(g) + 2SO₂(g)

Start with equation 3. It contains the first compound in the target (CS₂).

We have to reverse equation 3 and its ΔH to put the CS₂ on the left. We get equation A below.

A. CS₂(l) → C(s) + 2S(s); -

Now we eliminate C(s) and S(s) one at a time. Equation 1 contains C(s), so we write it as Equation B below.

B. C(s) + O₂(g) → CO₂(g);

We use Equation 2 to eliminate the S(s), but we have to double it to get 2S(s). We also double its

C. 2S(s) + 2O₂(g) → 2SO₂(g);

Finally, we add equations A, B, and C to get the target equation. We cancel things that appear on opposite sides of the reaction arrows.

A. CS₂(l) → C(s) + 2S(s); -

B. C(s) + O₂(g) → CO₂(g);

C. 2S(s) + 2O₂(g) → 2SO₂(g);

CS₂(l) + 3O₂(g) → CO₂(g) + 2SO₂(g);

Hope this helps.